Upholding Human Rights Within The Scope Of International Law Against The Palestinian - Najwa Zultan; Nadia Nur Elkameliati; Muhammad Syahdan Fauzi Abdul Fattah; Farrel Meikaputra Hendrawan; Dedi Mulyadi; Agustian Jatnika Putra (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
The purpose of this study is to analyze the early history of the background of the Israeli and Palestinian conflict that caused human rights violations that occurred during the conflict, especially in the Palestinian territories where many violations of this research were carried out by providing information and analysis of international cooperation to resolve the Israeli and Palestinian conflict through the realm of international law in upholding human rights against the Israeli community Method The approach in this study is to use a normative juridical approach, namely a legal research method that examines library materials or secondary data, thus this research method is also often referred to as doctrinal legal research sourced from secondary data, legal principles, positive legal rules from library materials, laws, and court decisions. "Upholding human rights within the scope of international law against the Palestinian people in the face of aggression by the State of Israel and its allies". This method allows researchers to gain an in-depth understanding of the issues under study and provides a strong legal foundation for their analysis The results showed that many human rights violations committed by Israel against Palestinians include deliberate killings, torture, inhuman resistance, arrests without cause, confiscation, and confiscation of Palestinian property and so on.  The implementation and enforcement of these rights in the Palestinian territories are often hampered by political complexity and ongoing conflict with Israel. Therefore, the promotion of human rights is imperative to ensure the completion of these rights through international cooperation and international law